Translokacja retabulum św. Katarzyny z Góry do katedry poznańskiej: nowe znaczenia średniowiecznego dzieła sztuki w powojennej Polsce - Frąszczak, Ksenia (Artium Quaestiones, 2025)
The main objective of this paper is to present the circumstances under which the late Gothic polyptych of St. Catherine from Góra (Guhrau), associated with the Jacob Beinhardt’s workshop, was translocated to the cathedral in Poznań in 1952. The paper discusses the institutional environment of the translocation, with the focus on the tension between institutions engaged in the process. It also covers the influence of the ideological significance given to the reconstruction by the representatives of the Church and the government. Prompted by the results of archaeological and architectural research conducted in the war-damaged building, restoration of the cathedral in the Gothic style was seen in 1940s and 1950s as an act imbued with symbolic meaning. However, it was interpreter differently by the clergy and by the ruling party. Thus the paper presents how the Retable of St. Catherine was inserted into two different systems of meaning constructed with regard to the rebuilding of the historic church, both of them referencing the resolution of World War II, the new role of the city of Poznań in the country in the context of the post-war border shift, as well as the upcoming Millenium of the Polish state and of Christianisation of Poland. In order to explain the role given to the Retable of St. Catherine in these visions, the author analyses press articles from the 1950s which discuss the polyptych. The post-war history of the altarpiece is juxtaposed against the fates of other retables translocated form the Recovered Territories to churches in other dioceses. Other attempts to acquire a Lower Silesian Gothic polyptychs as retables for the main altars of cathedral churches are also discussed. In doing so, the author highlights several circumstances which make the case of the Retable of St. Catherine being unique among post-war translocations of winged retables from Lower Silesia. The ideological use of the Retable in post-war Poland is compared to similar practices employed in regard to this polyptych by German art historians and art restorers in 1930s and 1940s. The text also attempts to answer the question of why the meanings associated with the Retable of St. Catherine in the post-war period are illegible to most contemporary viewers of the work, and why so many residents of Poznan are unaware of the Retable’s Silesian origins.